ENHANCED DERMAL DELIVERY OF NADIFLOXACIN USING LIPOSOMES - Shiny, Aharshikha; Toomu, Manicharan; Dhurke, Rajeshri Kashinath (International Journal of Applied Pharmaceutics, 2016)
Objective: The objective of the research work was to develop liposomal gel of nadifloxacin in order to achieve better permeation and high drug retention into the deeper layers of the skin for effective treatment of acne vulgaris. Methods: Various formulations were developed using different ratios of cholesterol and phospholipid (F1-F6) and evaluated for particle size distribution, shape, zeta potential, poly dispersibility index, entrapment efficiency. The best liposomal formulation was then incorporated into carbopol gel base and evaluated for drug retention studies, in vitro, and ex-vivo permeation rate and other parameters. Results obtained were compared with marketed product. Results: Formulation (F1) with an equimolar ratio of lipid and cholesterol had vesicles in the size range of 2 to 6 µm, a large unilamellar structure with highest percent entrapment of 71±3.50. Formulation (F1) released 79±0.98% of the drug in 12h. Low drug retention in skin i. e 40±1.64 % was observed for marketed product whereas Liposomal formulation (F1) showed high drug retention of 80±1.45 % in skin layers. Zone of inhibition for developed liposomal gel (F1) was better was compared to marketed gel. Zeta potential was found to be-45.6 with a polydispersity index of 0.412 indicating homogeneities and stability of vesicles. Conclusion: Developed liposomal formulation has better potential to treat acne due to high drug retention in skin layers.